The Effect of Video-Based Audiovisual Learning Media on the Science Learning Outcomes of Fourth-Grade Elementary School Students - Ni Gusti Ayu Nyoman Sugianti; La Sisi; Aris Suziman (CV. Gerasi Insan Nusantara, 2025)
Learning in Ilmu Pengetahuan Alam dan Sosial (IPAS) at the elementary school level continues to face challenges related to the limited use of varied and engaging instructional media, which may affect students’ understanding and learning outcomes. This study aimed to determine the effect of video-based audiovisual learning media on the IPAS learning outcomes of fourth-grade students at SD Negeri 3 Ranomeeto Barat. This study employed a quantitative approach with a pre-experimental method using a One-Group Pretest–Posttest Design. The sample consisted of 18 fourth-grade students selected through saturated sampling. Data were collected using a learning achievement test that had undergone expert validation and were analyzed using descriptive statistics, the Shapiro–Wilk normality test, the paired-samples t-test, and the N-Gain test with the assistance of IBM SPSS Statistics version 27. The results showed an improvement in students’ learning outcomes, with the mean score increasing from 71.11 on the pretest to 87.39 on the posttest. The normality test indicated that the data were normally distributed, allowing further analysis using parametric statistics. The paired-samples t-test produced a significance value of 0.001 (p < 0.05), indicating a statistically significant difference between students’ learning outcomes before and after the implementation of video-based audiovisual learning media. The average N-Gain score was 0.60, which falls within the moderate category. These findings indicate that video-based audiovisual learning media can improve students’ understanding and learning outcomes by presenting IPAS content through integrated visual and auditory elements. Therefore, video-based audiovisual learning media can serve as an effective and innovative alternative for supporting IPAS learning and improving elementary school students’ learning outcomes.